2021
DOI: 10.1088/2632-072x/ac4004
|View full text |Cite
|
Sign up to set email alerts
|

Poisson-distributed noise induces cortical γ-activity: explanation of γ-enhancement by anaesthetics ketamine and propofol

Abstract: Additive noise is known to affect the stability of nonlinear systems. To understand better the role of additive noise in neural systems, we investigate the impact of additive noise on a random neural network of excitatory and inhibitory neurons. Here we hypothesize that the noise originates from the ascending reticular activating system (ARAS). Coherence resonance in the γ-frequency range emerges for intermediate noise levels while the network exhibits non-coherent activity at low and high noise levels. The ana… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 43 publications
1
4
0
Order By: Relevance
“…Simultaneously, a constant input in these cortical layers is applied. As demonstrated in previous studies [ 60 , 64 ], the synchronous impact on both input and transfer function steepness is a direct result of a modulation by Poisson spiking activity in the ensemble, cf. the Appendix A.2 .…”
Section: Methodssupporting
confidence: 57%
See 2 more Smart Citations
“…Simultaneously, a constant input in these cortical layers is applied. As demonstrated in previous studies [ 60 , 64 ], the synchronous impact on both input and transfer function steepness is a direct result of a modulation by Poisson spiking activity in the ensemble, cf. the Appendix A.2 .…”
Section: Methodssupporting
confidence: 57%
“…To gain these insights, the neural model considers recent hypotheses on how tDCS affects synapses and neuronal populations. For instance, we assume that tDCS induces an intrinsic Poisson-noise activity in single neurons that represents a modulated input current and transfer function in the population [ 64 ]. This allows to describe the well-known modulated excitability by short-duration tDCS.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, Powanwe and Longtin [48] have described experimentally observed neural burst activity as an additive noise-controlled process and Powanwe and Longtin [49] have provided conditions under which two additive noisedriven biological systems share optimally their information. Moreover, previous theoretical neural population studies have demonstrated that additive noise can explain intermittent frequency transitions observed in experimental resting state electroencephalographic data [50], dynamical switches between two frequency bands induced by opening and closing eyes in humans [51], and the enhancement of spectral power in the γ -frequency under the anesthetic ketamine [52].…”
Section: Introductionmentioning
confidence: 94%
“…For completeness, it is important to mention quasi-cycle activity [52][53][54][55]. Mathematically, this is the linear response of a deterministically stable system to additive noise below a Hopf bifurcation.…”
Section: Introductionmentioning
confidence: 99%